First recorded isolation of Mycobacterium kansasii in a nonendemic setting - Jana Dajani, MD; Ali Shakhshir, MD; Ayham Sawalmeh, MD; Ameer Awashra, MD; Mo'tasem Dweekat, MD; Khaled Al-ali, MD; Ahmad Mohammad Adnan fatayer, MD (Radiology Case Reports)
Nontuberculous mycobacteria (NTM) are a diverse group of environmental mycobacteria found ubiquitously in soil and water, causing infections that typically arise from environmental exposure rather than person-to-person transmission. This case report documents the first known detection of Mycobacterium kansasii in our region, emphasizing the clinical challenges and diagnostic complexities associated with NTM infections. The case involves a 37-year-old male with a significant smoking history who presented with progressively worsening cough, significant weight loss, and bilateral cavitary lung lesions. Initial diagnostic efforts, including tests for tuberculosis and malignancy, were inconclusive. However, subsequent bronchoalveolar lavage confirmed the presence of M. kansasii, leading to a year-long treatment regimen. This report signifies a critical step in recognizing the burden of NTM infections in region, a region where comprehensive epidemiological data are lacking. The rising global incidence of NTM lung disease and its association with underlying lung conditions and immunocompromised states further underscore the importance of this case, particularly given the diagnostic overlap with more common conditions like tuberculosis. This case calls attention to the need for optimized local diagnostic criteria and the potential for NTM to be a causative agent of community-acquired pneumonia.